Strategy for Developing Rice Agribusiness in Rato Village, Lambu District, Bima District - Masnah Masnah; Kharismafullah Kharismafullah; Khairunnisah Khairunnisah (SENTRI: Jurnal Riset Ilmiah, 2026)
This research aims to determine the strengths and weaknesses (internal) as well as opportunities and threats (external) in the development of rice agribusiness as well as strategies for developing rice agribusiness in Rato Village, Lambu District, Bima Regency. Sampling was carried out using a purposive technique, namely where members were chosen deliberately for the development of rice agribusiness by tracing the sample population, namely 13 people involved. The data analysis used is to identify internal and external factors then use SWOT analysis through the IFAS and EFAS matrices, then use the IE matrix to see farmers' strengths. After that, use the SWOT matrix to get several alternative strategies. The results of the research that has been carried out show that the strategy for developing rice agribusiness in Rato Village is to develop agricultural technology, improve rice agribusiness, hone farmers' skills, use superior seeds, increase the amount of transportation and so that farmers can follow instructors' instructions regarding rice cultivation.